2005
DOI: 10.1097/01.aco.0000162841.02087.5c
|View full text |Cite
|
Sign up to set email alerts
|

Simulation technology in training students, residents and faculty

Abstract: Simulation is receiving increasing support as an educational tool and in its use for evaluation purposes. Research into this area is still somewhat limited. As the research impetus increases in the future, we may see simulation as a major focus in all disciplines with respect to its use in the improvement of patient safety. Team training, including both personality and attitudinal issues similar to those performed in other high hazard industries, may become increasingly evident in the literature in the coming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…[2728] It has also proved to be effective in both undergraduate and post graduate education as well as faculty development. [2930] Simulation can be used in the primary health care setting to improve confidence in performing life-saving skills,[31] clinical skills,[3233] communication skills,[34] and the quality of care for patients with chronic diseases such as diabetes mellitus and bronchial asthma. [3536] Such simulators as part task trainers, computer-based systems, virtual reality and the haptic system, simulated patients, simulated environment, and integrated simulators have been also used effectively to assess and evaluate clinical skills.…”
Section: Simulation Based Trainingmentioning
confidence: 99%
“…[2728] It has also proved to be effective in both undergraduate and post graduate education as well as faculty development. [2930] Simulation can be used in the primary health care setting to improve confidence in performing life-saving skills,[31] clinical skills,[3233] communication skills,[34] and the quality of care for patients with chronic diseases such as diabetes mellitus and bronchial asthma. [3536] Such simulators as part task trainers, computer-based systems, virtual reality and the haptic system, simulated patients, simulated environment, and integrated simulators have been also used effectively to assess and evaluate clinical skills.…”
Section: Simulation Based Trainingmentioning
confidence: 99%
“…9 Several other authors have highlighted the need for team training and IPE to improve patient safety and outcomes and suggest that simulation is the most viable and promising means for realizing this goal. [8][9][10][11][12][13][14] A study by Liaw et al 13 showed that by promoting open communication, shared information and decision making, mutual respect, and trust during the interprofessional simulation training, IPE achieves a positive transformation of stereotypes and attitudes toward nurse-physician collaboration. Another study found that although residents and nurses often relied on traditional methods of interaction during interprofessional training, they also demonstrated readiness for increased sharing of responsibilities, concluding that IPE should insist on better definition of respective roles and reinforced behaviors that have shown to enhance teamwork quality.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation can facilitate standardized skills practice and assessment, and when combined with global checklists, simulation-based assessment can help normalize continuing education standards for nurses across the workforce (e.g., Morgan & Cleave-Hogg, 2005;Landry et al, 2006;Gaba, 2009). In fact, some authors have called for incentive programs, such as insurance cost reduction, for institutions or individuals that engage in continuing simulation-based education (e.g., Gaba, 2004).…”
Section: (6) Ensure That Nurses Engage In Lifelong Learningmentioning
confidence: 99%